Makna Sosio-Teologis Melayani Menurut Roma 12:7 - Yonatan Alex Arifianto (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2020)
Christianity is inseparable from ministry either in a holistic mission or a church ministry. As one of the gifts given by God in believers who must be actualized to God and others through a special gift, namely the gift of serving. Using descriptive qualitative method, the writer analyzes and examines the meaning of the gift of service which is expected to increase understanding and can have an impact on God's servants. which the purpose of writing is to bring believers more active in serving through the gift of serving. By understanding Christian service in Romans 12: 7, it can be concluded that the gift of serving is a must for believers given to him by God. For that the servant is expected to be able and careful in understanding the theological review in Romans 12: 7, so that the servant realizes that the service entrusted is an honor given by God and is done with sincerity as the dedication of a believer who receives gifts based on the example of Jesus. Then interpret service in socio-theology, which makes the meaning of serving which must be actualized to God and others as part of being a blessing for the world. Kekristenan tidak lepas dari pelayanan baik secara misi holistik maupun pelayanan gereja. Sebagai salah satu dalam karunia yang diberikan oleh Tuhan dalam kepada orang percaya yang harus diaktualisasikan kepada Tuhan dan sesama lewat karunia khusus yaitu karunia melayani. Menggunakan metode kulaitatif deskriptif, penulis menganalisis dan mengkaji makna karunia melayani yang diharapkan dapat meningkatkan pemahaman dan dapat membawa dampak bagi para pelayan Tuhan. yang mana tujuan dalam penulisan ini untuk membawa orang percaya semakin giat dalam melayani lewat karunia melayani. Dengan memahami melayani menurut Kristen dalamRoma 12: 7, dapat disimpulkan bahwa Karunia melayani adalah sebuah keharusan bagi orang percaya yang kepadanya diberikan oleh Tuhan. Untuk itu pelayan diharapakan mampu dan cermat dalam memahami tinjauan teologis dalam Roma 12: 7, sehingga pelayan menyadari bahwa pelayanan yang dipercayakan adalah kehormatan yang diberikan Tuhan dan dikerjakan dengan kesungguhan sebagai dedikasi orang percaya yang menerima karunia yang didasari dari keteladanan Yesus. Lalu memaknai pelayanan dalam sosio-teologi, yang menjadikan makna melayani yang harus diaktualisasikan.